Du concept de situation dans les didactiques de l’histoire, de la géographie et de l’éducation à la citoyenneté - François Audigier (Recherches en Éducation)
After a certain fortune in its association with the word problem, the concept of situation is once again returned to the forefront with the didactics concerns of educational curricula by competences. These require necessarily a renewed reflection on the situations. Indeed, skills are built and implemented in situation. They also focus on specific objects. Thus, history, geography and citizenship education, the main social science disciplines present at the compulsory school, study human actions in past and present societies. The term situation therefore refers to two different realities: the teaching situation as it is organized and implemented by the teacher and the past or present social reality being studied. In this text, the author draws a course from the examination of some aspects of the relationship between skills and situations to the proposition of two times two distinctions to describe understand and analyze the teaching-learning situations. For the latter point, he relies on a research on Education for Sustainable Development led by a Frenchspeaking Swissresearchteam.